2019
DOI: 10.3389/fphar.2019.00898
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside III Enhances Anti-Tumor Response of NK Cells by Elevating NKG2D and IFN-γ

Abstract: Natural killer (NK) cells play an irreplaceable role in the development of colon cancer, in which antitumor function of NK cells was impaired. Astragaloside III is a natural compound from Astragalus that has been shown to have immunomodulatory effects in various systems. However, few studies have evaluated the antitumor effects of Astragaloside III through stimulating systemic immunity and regulating NK cells. In this study, flow cytometry, immunohistochemical analysis, and immunofunctional assays were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Astragalus is a plant that has been used in traditional chinese medicine for centuries, which is commonly used to treat certain diseases. Numerous studies reported that Astragalus could have some immunoregulatory and antitumor effects (10)(11)(12)(13). Recent studies demonstrated that Astragalus polysaccharides (APS), which are the major components of Astragalus, also have some antitumor and anti-fibrotic effects (11,14).…”
Section: Astragalus Polysaccharides Attenuate Pulmonary Fibrosis By Inhibiting the Epithelial-mesenchymal Transition And Nf-κb Pathway Acmentioning
confidence: 99%
“…Astragalus is a plant that has been used in traditional chinese medicine for centuries, which is commonly used to treat certain diseases. Numerous studies reported that Astragalus could have some immunoregulatory and antitumor effects (10)(11)(12)(13). Recent studies demonstrated that Astragalus polysaccharides (APS), which are the major components of Astragalus, also have some antitumor and anti-fibrotic effects (11,14).…”
Section: Astragalus Polysaccharides Attenuate Pulmonary Fibrosis By Inhibiting the Epithelial-mesenchymal Transition And Nf-κb Pathway Acmentioning
confidence: 99%
“…Aidi injection is composed of cantharidin, astragaloside, ginsenoside, elentheroside E, and syringin (Zhang et al, 2012;Zeng et al, 2016). The results from clinical and basic studies revealed that Aidi has an important antitumor, immunoregulatory, anti-inflammatory and antioxidative stress function (Duan et al, 2018b;Li et al, 2018;Zhou et al, 2018;Xiao et al, 2019a;Chen et al, 2019;Farag et al, 2019;Huang et al, 2019;Li et al, 2019;Qu et al, 2019;Zhang et al, 2019). The results of previous SRs/meta-analyses (Ma et al, 2009;Xiao et al, 2016;Wu et al, 2017a;Xiao et al, 2018a;Xiao et al, 2018b;Wang et al, 2018;Xiao et al, 2019b) demonstrated that Aidi in combination with chemotherapy showed significant improvements in tumor response, QOL, and OS rate, and decreases in ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…The active ingredients comprise the following main components: astragaloside (Re, Rb1, and Rg1), ginsenoside, cantharidin, elentheroside E, and syringin (Zhang et al, 2012;Zeng et al, 2016). These are purported to induce tumor cell apoptosis and to inhibit tumor cell proliferation and invasion (Duan et al, 2018b;Chen et al, 2019;Li et al, 2019), to reduce chemotherapy-related ADRs through anti-inflammation and antioxidative stress (Farag et al, 2019;Qu et al, 2019;Zhang et al, 2019), and to repair the host's antitumor immunity though upregulating the levels of peripheral blood lymphocytes (PBLs) (Li et al, 2018;Zhou et al, 2018;Huang et al, 2019). In clinic, Aidi in combination with GP has been widely used in the treatment of NSCLC (Lv et al, 2018;Zhang, 2018;Zhou, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…1D). Given the fact that NK cells can exert antitumor and anti-metastasis activities by secreting various effector molecules such as IFN-γ, perforin and granzyme B [12], we further detected the levels of IFN-γ, perforin and granzyme B in the tumor-bearing mice. It was found that high-dose of Tanshinol could effectively promote the release of above-mentioned killing mediators in the serum, which may be related to the activation and enhanced function of NK cells mediated by Tanshinol (Fig.…”
Section: Namementioning
confidence: 99%